Texturing and modeling (AP Professional, 1998)
Congratulations to Ken Perlin for his 1997 Technical Achievement Award from the Academy of Motion Picture Arts and Science Board of Governors, given in recognition of the development of "Turbulence", Perlin Noise, a technique discussed in this book which is used to produce natural appearing textures on computer-generated surfaces for motion picture visual effects. Dr. Perlin joins Darwyn Peachey (co-developer of RenderMan(R), also discussed in the book) in being honored with this prestigious award.